Ocrelizumab Impairs the Phenotype and Function of Memory CD8+ T Cells: A 1-Year Longitudinal Study in Patients With Multiple Sclerosis. Issue 2 (30th March 2023) - Mathias, Amandine; Pantazou, Vasiliki; Perriot, Sylvain; Canales, Mathieu; Jones, Samuel; Oberholster, Larise; Moulin, Michaël; Fenwick, Craig; Bernard-Valnet, Raphaël; Théaudin, Marie; Pot, Caroline; Du Pasquier, Renaud A.
Abstract : Background and Objective: Depleting CD20 + B cells is the primary mechanism by which ocrelizumab (OCRE) is efficient in persons with multiple sclerosis (pwMS). However, the exact role of OCRE on other immune cell subsets directly or indirectly remains elusive. The purpose of this study is to characterize the dynamics of peripheral immune cells of pwMS on OCRE. Methods: We collected blood samples from 38 pwMS before OCRE onset (T0) and at 6 and 12 months (T6, T12) after initiation. To cover the immune cell diversity, using mass cytometry time of flight, we designed a 38-parameter panel to analyze B, T, and innate immune cell markers and CNS migratory markers. In parallel, viral-specific CD8 + T-cell responses were assessed by the quantification of interferon-γ secretion using the enzyme-linked immunospot assay on cytomegalovirus, Epstein-Barr virus, and influenza stimulations. Results: Beside B-cell depletion, we observed a loss in memory CD8 + CD20 + and central memory CD8 + T cells but not in CD4 + CD20 + T cells already at T6 and T12 ( p < 0.001). The loss of memory CD8 + T cells correlated with a lower CXCR3 expression ( p < 0.001) and CNS-related LFA-1 integrin expression ( p < 0.001) as well as a reduced antiviral cellular immune response observed at both time points ( p < 0.001). Of note, we did not observe major changes in the phenotype of the other cell types studied. Seven of 38 (18.4%) patients in our cohort presented with infections while on OCRE; 4 of which were switched from dimethyl fumarate. Finally, using a mixed linear model on mass cytometry data, we demonstrated that the immunomodulation induced by previous disease-modifying therapies (DMTs) was prolonged over the period of the study. Discussion: In addition to its well-known role on B cells, our data suggest that OCRE also acts on CD8 + T cells by depleting the memory compartment. These changes in CD8 + T cells may be an asset in the action of OCRE on MS course but might also contribute to explain the increased occurrence of infections in these patients. Finally, although more data are needed to confirm this observation, it suggests that clinicians should pay a special attention to an increased infection risk in pwMS switched from other DMTs to OCRE.